Meliolaceae of Kerala, India - XXIV - H. BIJU and G.R. ARCHANA, V.B. HOSAGOUDAR*, D.K. AGARWAL, (Indian Phytopathology, 2007)
This paper gives an account of fungi belonging to the genera Amazonia and Meliola collected from Karnataka and Kerala States. Of these, Amazonia elaeocarpi, Meliola palakadensis, M. salaciicola are the new species, Irenopsis sidae var. abutili, Meliola kanniyakumariana var. brahmagiriense and M. tabernaemontanae var. wrightiae are the new varieties described and illustrated in detail.